New friends - Misra, Michelle; Chaffey, Samantha (New York : Aladdin, an imprint of Simon & Schuster Children's Publishing Division, 2016)
Ella is a trainee angel, and its her first day at the Guardian Angel Academy. But she's far from angelic, and can't help getting into all sorts of trouble!
Keywords: Angels -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Angels; Friendship; Schools; Fiction; Juvenile works; Fantasy fiction